Focus on the pulmonary involvement and genetic patterns in Birt-Hogg-Dubè syndrome: Literature review. (July 2020) - Marziali, Valentina; Geropoulos, Georgios; Frasca, Luca; Longo, Filippo; Patrini, Davide; Panagiotopoulos, Nikolaos; Crucitti, Pierfilippo
Abstract: Introduction: Brit-Hogg-Dubé syndrome (BHD) is a rare disorder that is estimated to affects about 600 families in the World. The disease-causing mutations is on FLCN gene which codes for folliculin. This protein has a role in different organs as skin, kidney and lung, thanks to the interaction with type I and II cadherins, RhoA activity and the regulation of AMPK, mTORC1 pathways and cell adhesion. The aim of our study is to focus on the manifestation of the syndrome, especially the pulmonary involvement, then on genetical analysis and on the available treatments. Material and methods: We collected 15 previous studies where we found medical history information, clinical manifestations, radiological and histological diagnosis and genetical analysis. Results: The prevalence of pneumothorax in patients with BHD syndrome was about 65%, but the lung involvement with multiple small cysts, localized especially in the lower part, was 85%. The prevalence of renal involvement in BHD patients ranged from 6.5% to 34%, while skin lesions ranged from 11% to 50%. More than 150 FLCN germline has been described, though the mutation in exon 11 is the most frequently detected, especially among Caucasian population. Conclusions: BHD syndrome is rare and usually the first manifestations appear in early age. In patients with these clinical and radiological characteristics we suggest taking a careful medical history, though the diagnosis of BHD syndrome should be confirmed with the analysis of FLCN gene. Highlights: FLCN mutation has been found to contribute to the pathogenesis of the syndrome. Main manifestations of BHD syndrome are skin lesion, kidney tumour, pulmonary cysts and spontaneous pneumothorax. Spontaneous pneumothorax used to occur in early age and usually with recurrence. Investigate family history of spontaneous pneumothorax, skin and renal lesions, is necessary to achieve the diagnosis.